Feasibility of implementing cytology‐based cervical cancer screening national program in Lebanon: A pilot study. Issue 1 (13th October 2022) - Seoud, Muhieddine; Jaafar, Iman; Hamadeh, Randa; Ammar, Walid; Atallah, David; El‐Kak, Faysal
Abstract: Objective: To review our national cervical cancer screening program using existing Ministry of Public Health primary healthcare centers (PHCs) and report the impact of women's knowledge, attitude, behavior, and practices on screening uptake and outcome. Methods: A cross‐sectional study on cervical cancer screening offered to sexually active Lebanese women aged 21 years and above visiting PHCs. Exclusions were history of complete hysterectomy, gynecologic cancers, and current pregnancy. Data were collected through a questionnaire and conventional cervical smear performed by trained healthcare providers and sent to one centralized cytopathology laboratory. Results: Of 12 273 eligible women, 1.7% had an abnormal cervical smear test including 161 atypical squamous cells (ASC) of undetermined significance, 6 atypical glandular cells of undetermined significance, 16 low‐grade squamous intraepithelial lesion (SIL), 17 ASC—cannot rule out high‐grade SIL, 11 high‐grade SIL, and one invasive carcinoma. Knowledge and attitudes significantly affected participation in screening; women lacking awareness had rarely undergone a cervical smear. Conclusion: In Lebanon, cytology‐based cervical cancer screening is feasible within the PHCs. Positive screen incidence was low. Despite previous campaigns, a low level of knowledge persists, and affects women's com with the screening guidelines. Advocacy and awareness activities by key healthcare providers may help to improve participation. Synopsis: Low knowledge level affects women's complian with screening guidelines. Advocacy and awareness activities by healthcare providers can improve participation in screening programs.